ANALISIS KINERJA KOPERASI PANCA EKA TAMA DI DESA MERANTI, KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Rindu Trianita; Sakti Hutabarat; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Cooperative of Panca Eka Tama has significant role in improving its members’ economy through various activities. Evaluation on the cooperative performance is an interesting topic to show how the cooperative run their business to improve the welfare of its members. The objective of this study is to analyse the performance of Panca Eka Tama Cooperative using financial ratio analysis, economic value added analysis, and financial analysis of cooperative during the last five years. This study using a case study method. Primary data were collected from the chairman, staffs and members of the cooperative while the source of secondary data were collected from related government and private institutions. The result of the study shows that the liquidity tends to vary in a positive way while the solvability declines gradually. However, the profitability and activity ratios of the cooperative fluctuated in a negative direction. The manager of the cooperative must take into account these financial indicators in order to make necessary actions to improve the cooperative’s performance.   Keywords: financial performance, liquidity, solvability, profitability, and activity